Hydrochemistry from time series station Boknis Eck from 2015 to 2023 - Hermann W Bange; Kastriot Qelaj; Helmke Hepach; Frank Malien (PANGAEA, 2024)
The dataset was acquired at the time-series station Boknis Eck (54.5°N and 10.0°E) at six standard depths (1, 5, 10, 15, 20, 25 m). The dataset contains data for temperature and salinity (CTD), nutrients (nitrate, nitrite, silicate, phosphate) and oxygen (sampled with a rosette sampler). The data are from 2015 to 2023.